Advances in research on RNA methylation and cancer radiotherapy resistance - Hui Liu; Hui Luo; Ming Jin; Zhen Zheng; Yang Xi; Kaitai Liu (Frontiers in Oncology)
RNA methylation is a type of reversible chemical modification in epitranscriptomics that influences gene expression by dynamically regulating RNA functions. RNA methylation comprises N6-methyladenosine (m6A), 5-methylcytosine (m5C), N7-methylguanosine (m7G), N1-methyladenosine (m1A), and 3-methylcytosine (m3C) modifications. These are dynamically controlled by a tripartite enzymatic system: methyltransferases (“writers”) add methyl groups, demethylases (“erasers”) remove them, and RNA-binding proteins (“readers”) recognize and interpret the modifications to mediate downstream biological effects. Extensive research has shown the importance of RNA methylation in the onset and progression of cancer. RNA methylation contributes to radioresistance in cancer cells through various mechanisms, affecting therapeutic outcomes. To date, the precise functions of RNA methylation in cancer radioresistance remain unclear. This review summarizes recent advances in m6A, m5C, m7G, and m1A methylation in cancer radioresistance regulation and discusses the clinical potential of precision therapeutic strategies targeting these methylation modifications.